JHEA, Volume 16, n° 1 & 2, 2018 - Full Issue - Journal System, (Journal of Higher Education in Africa, 2021)
Contents Editorial Elísio S. Macamo........................................................................v Introduction: Reclaiming the African Diaspora to Support African Higher Education Patrício V. Langa & Samuel Fongwa.............................................................vii African Diaspora and the Search for Academic Freedom Safe Havens: Outline of a Research Agenda Nelson Casimiro Zavale & Patrício V. Langa..............................................................1 Modelling an African Research University: Notes towards an Interdisciplinary, Cross-Cultural and Anticipative Curriculum Clapperton Chakanetsa Mavhunga.........................................................25 African Diaspora and its Multiple Academic Affiliations: Curtailing Brain Drain in African Higher Education through Translocal Academic Engagement Patrício V. Langa.......................................................................51 Navigating the Uncertain Path of Research Partnerships: The Role of ICT John Kwame Boateng & Raymond Asare Tutu.....................................................77 Moving Beyond Poststructural Paralysis: Articulating an Ethic of Diaspora Collaboration Nelson Masanche Nkhoma..........................................................95 Diaspora Collaboration and Knowledge Production in Africa: Reflections on Caveats and Opportunities Samuel Fongwa................................................................115 Advancing Collaboration between African Diaspora and Africa-based Scholars: Extracts of Interviews with Selected African Diaspora Scholars Patrício V. Langa, Patrick Swanzy & Pedro Uetela........................................135